Fuzzy Keyword Search over Encrypted Stego in Cloud - Dahake, Tanmay; Shaikh, Mir Sohail; Khandeparkar, Vipul; Panchal, Neerav; Bherde, Gajanan (International Journal of Computer Sciences and Engineering, 2025)
Today cloud is a relatively young and booming technological advancement. Cloud services are getting more and more popular these days, from online software to cloud storages like Google drive, one drive, Dropbox, etc. Smartphones and increasing internet connectivity are the main catalyst to this booming industry. The benefits that can be obtained from this technology are many like low cost, low maintenance and many more. Consumers now don’t have to worry about the storage space, now they can subscribe to cloud storage and avail much more data storage capacity at low cost compared to actual hardware. But there are many problems too, security and privacy is one of the major one. In this paper we will propose a solution for this problem in the context of cloud storage. We propose usage of cryptography and steganography. Cryptography converts ordinary information (plain text) into something that doesn’t make sense or incomprehensible information (cipher text). Steganography is concealment of information. Unlike cryptography it doesn’t attract attention, it just appears to be a normal data but within it a sensitive data is hidden. The other problem is data retrieval or searching. We propose using fuzzy logic for this.Fuzzy keyword search incredibly improves framework ease of use by giving back the coordinating data when clients seeking inputs precisely coordinate the predefined keywords or the nearest conceivable coordinating data in view of keyword similitude semantics, when careful match comes up short.